(untitled) (Economic and Political Thought, 2023)
Cities embody the idea of change, being at the same time the impulse and driving force of this change. Urban agriculture is also a part of this process, constituting one of the contemporary perspectives of the urban future. Urban agriculture in its current form of integration is a new functional element of cities gaining increasing importance for the future cities i.e. sustainable, green, resilient and smart cities.